2020
DOI: 10.1080/12298093.2020.1735765
|View full text |Cite
|
Sign up to set email alerts
|

Soil Application of Metarhizium anisopliae JEF-314 Granules to Control, Flower Chafer Beetle, Protaetia brevitarsis seulensis

Abstract: Root-feeding Scarabaeidae, particularly white grubs are considered among the most harmful coleopteran insect pests in turfgrass. In this work, sixteen entomopathogenic fungal species were assayed against flower chafer beetle, Protaetia brevitarsis (Coleoptera: Scarabaeidae) and Metarhizium anisopliae JEF-314 showed high virulence. The control ability of the isolate JEF-314 has been in detail tested for a model insect flower chafer beetle. Further analyses showed insect stage-dependent virulence where the funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Kim et al . (2020) confirmed that millet‐based solid cultured granules of M. anisopliae were effective against soil‐dwelling pest insects. Conidiation is highly influenced by the composition of nutrients.…”
Section: Discussionmentioning
confidence: 79%
“…Kim et al . (2020) confirmed that millet‐based solid cultured granules of M. anisopliae were effective against soil‐dwelling pest insects. Conidiation is highly influenced by the composition of nutrients.…”
Section: Discussionmentioning
confidence: 79%
“…In the two-choice arena without food, the beetles of both sexes flew and crawled around the arena continually, resulting in no significant preference to 4-methylanisole (unpublished data). Inspired from the phenomenon that WSFC aggregations are always observed on their food 1 , 17 , 20 , we deduced that WSFCs release aggregation pheromone when they find suitable food sources. In each compartment of the arena, we added odorless agar-gel as food or residence place for WSFCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that Cetoniinae beetles, the most frequent flower visitors, not only play an important role in plant pollination 32 34 but also are serious pests of flowers and fruits because they usually attack and feed on blooming flowers and ripe fruits 35 . Polyphagous WSFC adults feed on the flowers and fruits of dozens of plant species 1 , resulting in the possibility that 4-methylanisole identified from WSFC volatiles originated in their foods sources. To control for this, we fed the WSFCs in volatile collection with only water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entomopathogenic fungi (EPFs), such as species of Beauveria , Metarhizium , Isaria (recently named Akanthomyces ), and Lecanicillium , have been considered as biocontrol agents for the management of agricultural, forest, and ornamental insect pests to overcome chemical pesticide‐mediated resistance, environmental toxicity, and residual issues 1 . EPFs have relatively broad host spectrums, but their pathogenicity and virulence are varied depending on the species and even different strains of the same species 2 . During infection by EPFs, they need to overcome the host insect self‐defense, including the exoskeleton/cuticle and the innate immune system.…”
Section: Introductionmentioning
confidence: 99%